Seeing the Trees From the Forest: Challenges in Subgroup Analysis-Based Guidelines in Oncology - Rotem, Ofer; Geiger, Karyn Revital; Hanovich, Ekaterina; Moskovitz, Mor; Kurman, Noga; Reinhorn, Daniel; Peretz, Idit; Yerushalmi, Rinat; Stemmer, Salomon M. (Oncology Reviews, 2024)
As clinical trials in oncology require substantial efforts, maximizing the insights gained from them by conducting subgroup analyses is often attempted. The goal of these analyses is to identify subgroups of patients who are likely to benefit, as well as the subgroups of patients who are unlikely to benefit from the studied intervention. International guidelines occasionally include or exclude novel medications and technologies for specific subpopulations based on such analyses of pivotal trials without requiring confirmatory trials. This Perspective discusses the importance of providing a complete dataset of clinical information when reporting subgroup analyses and explains why such transparency is key for better clinical interpretation of the results and the appropriate application to clinical care, by providing examples of transparent reporting of clinical studies (lung cancer) and examples of incomplete reporting of clinical studies (breast cancer).